Faktor Penghambat Implementasi Proyek Transportasi Masal berbasis Rel di Surabaya dengan Skema Kerjasama Pemerintah dengan Badan Usaha - Erfandi Zen Variamen; Mohammad Arif Rohman (Jurnal Aplikasi Teknik Sipil, 2021)
Public Private Partnership (PPPs) is one of the financing solutions in fulfilling infrastructure development for better public services. The rapid rate of population growth in the city of Surabaya is a challenge in developing transportation infrastructure. The alternative strategy is to revive rail-based mass transportation or called Tram. The purpose of this study is to determine the barriers in the implementation of the PPP scheme fo the Tram project. The research variables were obtained from literature review and were divided into 6 groups, namely Social, Legal, Economic, Environmental, Political, and Technology (SLEEPT). The research data was acquired based on four experts’ opinion in this area. Relative Important Index (RII), Confidence Interval (CI), and Pareto Diagram were employed to analyse the data. According to Pareto Diagram (81%), it was found that the economic variable had the two highest indicators, namely "High PPP procurement costs" with an RII value of 0.83 and "Weak access to PPP financing" with value of 0.77. Meanwhile, the legal variable has one indicator with the lowest value, namely the "Lack of Flexibility in Implementation" indicator with an RII value of 0.57. -----------------------------------------------------------Kerjasama Pemerintah Badan Usaha (KPBU) merupakan salah satu solusi pembiayaan dalam pemenuhan infrastruktur untuk pelayanan publik yang lebih baik. Pesatnya laju pertumbuhan penduduk di kota-kota besar seperti Surabaya menjadi tantangan dalam mengembangkan infrastruktur transportasi, berbagai alternatif strategi pun bermunculan, salah satunya menghidupkan kembali transportasi massal berbasis rel. yaitu Tram. Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor penghambat dalam pelaksanaan skema KPBU dalam pengadaan Tram. Variabel-variabel yang terdapat dalam penelitian ini diperoleh dari studi literatur. Teknik pengumpulan data yang digunakan adalah purposive sampling. Dalam penelitian ini dilakukan survei pendahuluan bersama expert kemudian dilakukan survei kuesioner utama. Selanjutnya dilakukan analisis dengan menggunakan Relative Important Index (RII), Confidence Interval (CI), dan Diagram Pareto. Dari hasil tersebut ditemukan 13 variabel yang dianggap sebagai faktor penghambat